Assessing the prevalence and antibiotic susceptibility patterns of S. aureus bacteria isolated from Iraqi women with vaginosis - Mahmmod, Suhad Saad; AlHadban, Wedean Ghassan (Iraqi Journal of Science, 2022)
Bacterial vaginosis (BV) is a common infection that occurs when the number of lactobacillus spp. bacteria (vaginal flora) decreases in the vaginal canal. The study aimed to determine the prevalence of Staphylococcus aureus within vaginosis in order to emphasize the importance of early detection and treatment. Totally, 90 vaginal swabs were collected using speculum and swabbing. The vaginal swabs were subjected to standard microbiological testing, which included microscopy, cultures (Blood agar and Mannitol salt agar), and antibiotic sensitivity testing. The results showed that out of 90 samples, only 40 S.aureus isolates were collected. S. aureus isolates showed maximum sensitivity to gentamicin and high resistance to Cefoxitin, Erythromycin, Azithromycin, and moderate resistance to Clindamycin, Rifampicin, Ciprofloxacin, and Doxycycline. Regarding molecular detection of mecA, the results revealed that out of 40 S. aureus isolates only 22 isolates have this gene. This study concludes that S. aureus (MRSA) was the most prevalent within vaginosis with high resistance to most antibiotics.